2022
DOI: 10.3847/2041-8213/ac905a
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Distribution on the Moon

Abstract: The Moon is significantly depleted in volatile elements when compared to Earth, an observation that has resulted in various formation scenarios leading to the loss of volatiles. Sodium is a moderately volatile element that is a lithophile, which can be utilized as a tracer of the volatile history in planetary bodies. It is also well observed in the exosphere of several bodies in our solar system and exoplanetary systems. But lunar surface sodium abundances have so far been measured only in samples brought back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The discrepancy of excessive Na 2 O is primarily due to inherent differences in the compositions of terrestrial rocks and lunar rocks (Narendranath et al 2022), and it highlights the need for more detailed study of the samples. It is inevitable that some samples have excessive Na content since sourcing materials from Earth makes it challenging to match precisely.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy of excessive Na 2 O is primarily due to inherent differences in the compositions of terrestrial rocks and lunar rocks (Narendranath et al 2022), and it highlights the need for more detailed study of the samples. It is inevitable that some samples have excessive Na content since sourcing materials from Earth makes it challenging to match precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Sarantos et al (2023) demonstrated that these velocities did not fit the line width measurements of sodium around the Moon; instead, the broader and more energetic distribution proposed by Mura et al (2009) explained the lunar measurements. Sarantos et al (2023) attributed the difference between the experiment and the lunar observations to the much lower coverage of adsorbed sodium on the Moon, approaching one-thousandth of a monolayer (Narendranath et al 2022), and citing laboratory evidence that release at coverages near a monolayer is less energetic than from a "bare" substrate. Thus, PSD speeds need to be quantified as a function of adsorbate coverage.…”
Section: Characterization Of the Dependency Of The Ejection Mechanism...mentioning
confidence: 99%